Large rivers as complex adaptive ecosystems. (6th June 2019) - Thoms, Martin; Sheldon, Fran
Abstract: Large rivers dominate the world's terrestrial surface, yet we are still learning of their structure, how they function, and whether they are different not only from each other, but also from smaller rivers. There is a benefit in framing large rivers as complex adaptive systems, as they contain essential features of these entities, the emergent properties of which are nonlinear and often display unpredictable behaviour in space and time, contagion, and modularity. Large rivers are also social–ecological systems with a high degree of coupling between natural and human components. The manuscripts in this special issue highlight these fundamental properties for large river ecosystems from different geographic regions of the world. This special issue is dedicated to three former editorial board members of River Research and Applications. The loss of Professors Bryan Davies (University of Cape Town, South Africa), Jay O'Keefe (Rhodes University, South Africa), and Keith Walker (University of Adelaide, Australia) leaves a great gap and a rich memory bank in river science—especially large river ecosystems.